Wushu as a tool for motor, cognitive and socioaffective development at school: an exploratory study (Revista de Artes Marciales Asiáticas, 2017)
The present work investigated the use of wushu at school by Physical Education teachers (PEF) as a tool for the motor, cognitive and socioaffective development, and compared practitioners and non-practitioners in concept, understanding and application of wushu resignified practices in Elementary School grades I and II in São Paulo, Brazil. For this purpose, 40 PEFs were assigned to one of two groups, wushu Practitioners (PW, n=27) or Non wushu Practitioners (NPW, n=13). All participants answered a questionnaire composed of 11 objective questions about the wushu practice by schoolchildren, with answers ranging on four levels ("does not attend", "partially", "fully" and "exceeds"). The Mann Whitney test was used to compare the responses, p